Analisis Nilai-Nilai Pendidikan Islam Dalam Q.S. Al-An’am 74-79 - Khalid Ramdhani Faturrahman (STAI Siliwangi Bandung, 2017)
Today, in this digital generation, there are so many educational concepts and theories that adopted and applied from western educational experts in Islamic education, a dozen of academics today is glorifying proudly by the concept which born fromfreedom worshiper (Liberty), whereas holy Qur'an very loaded full with educational concepts and theories. If all of theexperts develop these things, it will become a valuable jewelry for the world of Islamic education. We know the great scholar figures such as Al Ghazali, Ibn Sina, Al Khawarizmi, Muhammad Qutb, Muhammad Abduh, Abdullah Nasih ulwan, etc. The figures of Islamic Education whose concepts are inspired by the values ​​of Islamic education contained in Al-Qur'an. Therefore it is necessary to develop studies and research on the Islamic Education Value which is directly excavated from the main source is QS. al-An'am 74-79. This research is a qualitative research that uses historical approach because this study examines the data that occurred in the past by using historical facts. Data of this research were collected by using documentation method. The method of analysis is the method of content analysis (content analysis). The technique of this research for making inimitable inferences and with correct data and taking into account the context. In addition, this study also uses the method description of the analysis of the collected materials described, interpreted, compared to the similarities and differences with certain phenomena taken form similarities then drawing the conclusions.